Corporate Factors Influencing Holding Period of Stock: An Analysis of Market Capitalization Threshold - Fonna, Rizki Putri Nurita; Diantimala, Yossi; Priantana, Riha Dedi (Journal of Accounting Research, Organization and Economics, 2022)
Objective This study examines the effect of corporate factors on holding period of common stock. The main corporate factors tested are information asymmetry, firm value, earnings per share, and other corporate factors profitability, company size, leverage, and liquidityare selected as control variables.Design/methodology The samples consist of 876 observations of companies listed on the Indonesia Stock Exchange for 2017-2020. Samples were grouped using the threshold method based on their market capitalization to capture the different impacts based on certain conditions. To examine the hypotheses, we employed multivariate analysis with the threshold method.Results The results show that market capitalization contributes to determining the corporate factors' effect on the holding period of stock. Simultaneously, corporate factors affect significantly the holding period of stock. The increases in firm value, earnings per share, profitability, leverage, and corporate size extend the holding period. However, the emergence of information asymmetry precisely motivates investors to accelerate the holding period.Research limitations/implications This research did not consider the impact of the Covid 19 pandemic on data even it used data for 2020 (at the onset of pandemic). For future reseach, we suggest to consider the issue of the Covid 19 pandemic in examining the effect of corporate factors on holding period of stock.Novelty/Originality This study differentiates the samples based on their capitalization value as the novelty. Previous research did not classify the sample based on its capitalization value so large-value stocks are treated the same as small-value stocks. Actually, investors treat these three groups of stocks in different ways